Effect of including historical height and radius BMD measurement on sarco‐osteoporosis prevalence. Issue 1 (8th August 2012) - Buehring, Bjoern; Krueger, Diane; Binkley, Neil
Abstract : Background: A clinical need exists to improve identification of those who will sustain fragility fractures. Individuals with both osteoporosis (OP) and sarcopenia (SP), so‐called "sarco‐osteoporosis" (SOP), might be at higher fracture risk than those with OP or SP alone. Approaches to facilitate SOP identification, e.g., use of tallest historical rather than current height and inclusion of radius bone mineral density (BMD) measurement, may be of benefit. This study examined the effect of advancing age on SOP prevalence with and without use of historical tallest height and radius BMD measurement. Methods: Adults age 60+ underwent dual‐energy X‐ray absorptiometry (DXA) BMD and total body composition measurement. OP and SP were defined using standard criteria: T‐score ≤−2.5 at the lumbar spine or hip and appendicular lean mass (ALM)/current height 2 <5.45 kg/m 2 (female) and <7.26 kg/m 2 (male). Proposed "sensitive" SP criteria used historical tallest height instead of current height, while "sensitive" OP criteria added the 1/3 rd radius T‐score. The primary outcome was SOP prevalence by decade (60–69, 70–79, 80+). Results: A total of 304 individuals (146 M/158 F) participated. OP, SP and SOP prevalence were higher in older adults and increased ( p < 0.05) with the "sensitive" criteria. SOP prevalence was lower than that of OP or SP and increased (standard/sensitive) criteria from 1.1 % / 4.5 % in the 60–69 years age group to 10.4 % / 21.9 % in the 80+ years age group. Conclusions: SOP prevalence is higher in older adults. Use of historical tallest height and 1/3 rd radius BMD increases SOP prevalence. Future studies need to assess whether having SOP increases fracture risk and whether use of tallest height and/or one‐third radius BMD improves fracture risk prediction.